New Understandings of Current Information Literacy Instruction Practices: Informing our Scholarship and our Teaching - Julien, Heidi; Latham, Don; Gross, Melissa (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2018)
This paper examines the implications of findings from a recent survey of academic librarians with teaching responsibilities in U.S. academic libraries, for what they can suggest to library and information science scholars in terms of research questions, and for how they can inform our preparation of future librarians.